2020
DOI: 10.14444/7132
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Analysis of Deep Learning Algorithms for Reporting of Routine Lumbar MRI Scans

Abstract: Background: Artificial intelligence could provide more accurate magnetic resonance imaging (MRI) predictors of successful clinical outcomes in targeted spine care.Objective: To analyze the level of agreement between lumbar MRI reports created by a deep learning neural network (RadBot) and the radiologists' MRI reading.Methods: The compressive pathology definitions were extracted from the radiologist lumbar MRI reports from 65 patients with a total of 383 levels for the central canal: (0) no disc bulge/protrusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…This model performed well on the holdout dataset with an AUC of 0.94 and F1-score of 0.82. These performance metrics are similar to the best performing lumbar spine models that have been previously published 39 , 41 – 43 .…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This model performed well on the holdout dataset with an AUC of 0.94 and F1-score of 0.82. These performance metrics are similar to the best performing lumbar spine models that have been previously published 39 , 41 – 43 .…”
Section: Discussionsupporting
confidence: 73%
“…This model performed well on the holdout dataset with an AUC of 0.94 and F1-score of 0.82. These performance metrics are similar to the best performing lumbar spine models that have been previously published 39,[41][42][43] . We generated CAMs using example images from the testing dataset that were classified correctly (true positives) and incorrectly (false negatives).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Weakness of intervertebral disc's own anatomical factors: human intervertebral disc blood circulation gradually lacks in adulthood, and its self-repair ability becomes worse. Genetic factors: there are reports of familial incidence of lumbar disc herniation [ 17 ]. Congenital abnormalities of the lumbosacral: sacralization of the lumbar spine, hemivertebral deformity, asymmetry of the articular process, etc., change the stress on the lower lumbar spine, which is prone to degeneration and injury.…”
Section: Signs Of Lumbar Disc Herniation In Mri Diagnosismentioning
confidence: 99%
“…Cheung and Luk [ 16 ] reported that the accuracy of MRI in the diagnosis of intervertebral disc herniation is significantly higher than that of CT, and the accuracy of the diagnosis of intervertebral disc herniation and free intervertebral disc nucleus pulposus is 100%, which is significantly higher than that of CT examination of 88% and 50% LDH. The total detection rate of LDH by MRI is 96.67%, which is significantly higher than 71.67% of CT. For the diagnosis of lumbar facet joints in the comparison of CT and MRI, LewandrowskI et al [ 17 ] believe that MRI is an indispensable tool. The evaluation accuracy of FJ degeneration degree is 94% of CT. Osteophyte hyperplasia, gas accumulation in facet joints, and vacuum phenomenon will affect the accuracy of articular cartilage thickness measurement.…”
Section: Mri Study Of Lumbar Disc Herniationmentioning
confidence: 99%